Предмет: Алгебра,
автор: lej1999
Выразите из уравнения переменную х :
6х+12у=-24
Ответы
Автор ответа:
0
6х + 12у = -24
6х = -24 - 12у
х = (-24 - 12у) / 6
или так
6х + 12у = -24
6х = -24 - 12у
6х = -12 * (2 + у)
х = (-12 * (2 + у)) / 6
х = -2 * (2 + у)
6х = -24 - 12у
х = (-24 - 12у) / 6
или так
6х + 12у = -24
6х = -24 - 12у
6х = -12 * (2 + у)
х = (-12 * (2 + у)) / 6
х = -2 * (2 + у)
Автор ответа:
0
пожалуйста
Похожие вопросы
Предмет: Русский язык,
автор: 95lineForever
Предмет: Физика,
автор: logicheskayaptichka
Предмет: Литература,
автор: pavellebedev07
Предмет: Математика,
автор: vlad220201